Novos registros e checklist das espécies de Thysanoptera do Pampa Brasileiro - Cavalleri, Adriano; Gonçalves, Stephanie S. (Entomological Communications, 2022)
We present here the first checklist of the thrips of the Brazilian Pampa, which is a grassland region with sparse shrub and tree formations. This work involved observations of specimens deposited in scientific collections and surveys carried out in South Brazil in the last two decades. We listed 128 named species of Thysanoptera from the Pampa, with six new records from Brazil: Allothrips megacephalus megacephalus Hood, 1908; Aneristothrips rostratus De Santis, 1957; Compsothrips hoodi (De Santis, 1958); Holopothrips urinator De Santis, 1957; Rhinoceps jansei Faure, 1949 and Treherniella atrata De Santis, 1963.